Protective Effect of Ricinus communis Leaves Extract on Carbon Tetrachloride Induced Hepatotoxicity in Albino Rats: Hepatoprotective effect of Ricinus communis leaves extract - Evan Sabina Prince ,; Poorna Parameswari,; Evan Sabina Prince,; Rasool Mahaboob Khan, (Iranian Journal of Pharmaceutical Sciences, 2011)
Ricinus communis Linn. (Euphorbiaceae) is a soft wooded tree widely prevalent throughout tropics regions of the world which have a warm temperature. In the Indian system of medicine, the leaves, roots and seed oil of this plant have been used for the treatment of inflammation and liver disorders for a long time. In the present study, the protective effects of ethanol extract of Ricinus communis L. leaves on carbon tetrachloride-induced liver damage were investigated in rats. Results were compared with those of silymarin, a standard hepatoprotective drug. It was found that an increase in the activities of serum transaminases and the level of liver lipid peroxidation, protein, glycogen and the activities of acid and alkaline phosphatase in liver induced by CCl4 were significantly inhibited by treatment with Ricinus communis ethanolic extract (250/500mg/kg b.wt). In addition, the depletion of glutathione level and adenosine triphosphatase activity observed in the CCl4-induced rat liver were effectively prevented by treatment with Ricinus communis ethanolic extract (250/500mg/kg b.wt). Histopathological examination further confirmed the hepatoprotective activity of Ricinus communis ethanol extract when compared with the CCl4-induced control rats. In conclusion, these results indicate that the ethanol extract of Ricinus communis ethanolic extract exhibits hepatoprotective action.